The age of empire Britain's imperial architecture from 1880-1930 - Aslet, Clive 1955- (Aurum Press, 2015)
The Age of Empire is a lavishly illustrated celebration of the architectural legacy of the British Empire and its ability to create buildings that remain as awe-inspiring as when they were first built.